Onychophagia Induced Melanonychia, Splinter Hemorrhages, Leukonychia, and Pterygium Inversum Unguis Concurrently - Sezin Fıçıcıoğlu; Selma Korkmaz (Case Reports in Dermatological Medicine)
Onychophagia, which refers to compulsive nail-biting behavior, is common among children and young adults. Onychophagia can cause destruction to the cuticle and nail plate, leading to shortening of nails, chronic paronychia, and secondary infections. Relatively uncommon effects include pigmentary changes, such as longitudinal melanonychia and splinter hemorrhages. We report a case of a young adult with longitudinal melanonychia, splinter hemorrhages, punctate leukonychia, and pterygium inversum unguis, concurrently induced by onychophagia. Importantly, patients usually do not report this behavior when asked about nail-related changes. Even upon questioning, they may deny nail-biting behavior. As in many other dermatological disorders, dermoscopy can be helpful in the diagnosis of nail disorders.